2022
DOI: 10.1002/edn3.277
|View full text |Cite
|
Sign up to set email alerts
|

The artemis package for environmental DNA analysis in R

Abstract: Given these strengths, sampling for and detecting eDNA using quantitative polymerase chain reaction (qPCR) have gained popularity over the past 20 years (Dejean et al., 2012;Moyer et al., 2014) and are now broadly used to sample and indirectly infer the presence of taxa in a variety of aquatic environments. However, widespread sampling and detection of eDNA by ecologists and conservation biologists are unstandardized, and the field is in need of standards for statistical analysis and reporting (Fediajevaite et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…This study was primarily focused on M. temminckii detection, rather than optimizing a published qPCR assay to confidently quantify sample eDNA copy number. Therefore, low qPCR reaction efficiencies, which were generally ignored, may have resulted in non‐detections for samples with low eDNA concentrations typical of this species (Espe et al., 2022; Mauvisseau et al., 2019). Future studies may improve M. temminckii eDNA detection performance by re‐optimizing the qPCR assay for this species.…”
Section: Discussionmentioning
confidence: 99%
“…This study was primarily focused on M. temminckii detection, rather than optimizing a published qPCR assay to confidently quantify sample eDNA copy number. Therefore, low qPCR reaction efficiencies, which were generally ignored, may have resulted in non‐detections for samples with low eDNA concentrations typical of this species (Espe et al., 2022; Mauvisseau et al., 2019). Future studies may improve M. temminckii eDNA detection performance by re‐optimizing the qPCR assay for this species.…”
Section: Discussionmentioning
confidence: 99%
“…where y i,j,k is the measured replicate copy number and σ rep is the replicate-level copy number measurement error on the log scale, which could be a function of site, sample, or replicate covariates. Because 1) we condition the quantification process on positive detections and 2) copy number measurements may be censored from below by η q (Espe et al, 2022), the observed replicate-level quantitative data, y obs i,j,k , are:…”
Section: Observation Modelmentioning
confidence: 99%
“…Further, eDNA sampling can be a particularly useful tool for aquatic invasive species monitoring, potentially allowing for early detection and eradication (Larson et al, 2020; Morisette et al, 2021; Sepulveda et al, 2020). However, across many applications of eDNA monitoring in aquatic environments, the reliability of ecological inference can be reduced by 1) uncertainty in the source location of detected eDNA (Carraro et al, 2018; Jo and Yamanaka, 2022) and 2) difficulties measuring site and sample eDNA concentrations with minimal bias while accounting for all relevant sources of uncertainty (Ellison et al, 2006; Shelton et al, 2019; Espe et al, 2022). Both of these factors have the potential to reduce the effectiveness of eDNA sampling for management action, depending on their magnitude and how well they are addressed in experimental/monitoring design and statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…io/ artem is/ index. html) is one such model, developed and tested in the SFE specifically for eDNA qPCR requirements (Espe et al 2022). The analytical framework accommodates biases such as those that arise from qPCR "censored" data, when the amount of detected eDNA occurs at or below the threshold of detection for an assay (Espe et al 2022).…”
Section: Data Interpretationmentioning
confidence: 99%
“…html) is one such model, developed and tested in the SFE specifically for eDNA qPCR requirements (Espe et al 2022). The analytical framework accommodates biases such as those that arise from qPCR "censored" data, when the amount of detected eDNA occurs at or below the threshold of detection for an assay (Espe et al 2022). Purposefully designing studies under realistic circumstances is particularly important for management applications of eDNA data and can aid decision making by quantifying uncertainty in survey results.…”
Section: Data Interpretationmentioning
confidence: 99%